(untitled) (Research, Society and Development, 2022)
This work problematizes the use of diversified educational spaces for the teaching of Natural Sciences in Basic Education. To this end, semi-structured interviews were conducted with open questions about the teacher’s experience, intellectual training, daily teaching practices and factors that positively or not interfere in this process. Thus, it is emphasized that the main objective was to analyze the teaching discourses of four professors belonging to different educational institutions, through the software Atlas.ti., through the establishment of six analytical codes, namely: teacher training, teaching practice, teaching resources, pedagogical documents, advantages of activities in diversified educational spaces and difficulties in working in diversified educational spaces. From this, regarding the relations between thought (discourse) and lived (practice), it was possible to conclude that the main difficulties are the lack of adequate teacher training, excessive bureaucracy, and lack of financial investments for displacements and teaching materials, even though all teachers reinforced the importance of “diversified spaces”. To this end, the concept of “social representation” by Moscovici (2007) (2009) and the dialogical conception of language from the perspective of Bakhtin (1999) were used as a theoretical reference since it is a social product; added to the discussions on education, teaching and learning of Vygotsky (1999), Morin (2013) and Trilla (2008).